Limosilactobacillus reuteri prevents progression of ankylosing spondylitis in mice by restoring gut microbiota-metabolism homeostasis - Lianjun Yang; Ke You; Kun Wang; Bin Liu; Tao Chen; Zhifei Cui; Dawei Zhang; Zhihai Su; Xiang Liu; Hai Lu (Journal of Translational Medicine)
Abstract Background Ankylosing spondylitis (AS) is a chronic inflammatory disease characterized by progressive spinal fusion and systemic inflammation. Recent studies suggest that gut microbiota plays a crucial role in the pathogenesis of AS. Methods This study investigated the therapeutic effects of Limosilactobacillus reuteri (L. reuteri) on AS progression and its underlying mechanisms using a proteoglycan (PG)-induced mouse model. Female BALB/c mice (n = 10/group) were randomized into control group, PG group and PG + L. reuteri group. Disease severity was assessed via arthritis scores, Micro-CT images, and histopathology. Serum cytokines (IL-1β, IL-18, IL-17A, IL-23) were measured by ELISA. Intestinal barrier integrity was evaluated using FITC-dextran permeability, immunofluorescence (ZO-1, occludin), and colon histology. Gut microbiota (16S rRNA sequencing) and fecal metabolites (untargeted metabolomics) were analyzed. AhR/NLRP3 pathway activity was assessed via qRT-PCR (AhR, CYP1A1, CYP1B1, and NLRP3). Results Our findings demonstrated that L. reuteri significantly alleviated AS progression, as evidenced by reduced joint swelling and erythema, alongside a decreased arthritis index and paw thickness. Furthermore, treatment with L. reuteri resulted in a marked reduction in serum levels of pro-inflammatory cytokines, including IL-1β, IL-18, IL-17A, and IL-23, indicating its potential to modulate systemic inflammation. Additionally, L. reuteri enhanced intestinal mucosal barrier function, as demonstrated by improved histopathological integrity, reduced intestinal permeability, and restored expression of tight junction proteins ZO-1 and occludin. Moreover, L. reuteri treatment restored gut microbiota composition and metabolite profiles, aligning them more closely with control groups. Notably, L. reuteri may exert its effects partially through the AhR/NLRP3 pathway, as evidenced by increased mRNA levels of AhR, CYP1A1, and CYP1B1, along with reduced NLRP3 expression. Conclusion In conclusion, L. reuteri effectively prevents the progression of AS in mice by restoring gut microbiota-metabolism homeostasis and modulating inflammatory pathways, highlighting its potential as a therapeutic agent for AS.